2017
DOI: 10.1128/genomea.00980-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Novel Subgenotype of Porcine Reproductive and Respiratory Syndrome Virus Strain JX/CH/2016, Isolated in Jiangxi, China

Abstract: We sequenced the complete genome of porcine reproductive and respiratory syndrome virus (PRRSV) strain JX/CH/2016. Phylogenetic analysis based on the sequences of the open reading frame 5 (ORF5) gene revealed that this strain belongs to subgenotype IV. This is the first report of the complete genome sequence of PRRSV-IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
1
0
0
Order By: Relevance
“…Moreover, the QYYZ-like strains (sublineage 3.5) were prevalent only in mainland China. According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 16 , 23 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China.…”
Section: Resultssupporting
confidence: 78%
“…Moreover, the QYYZ-like strains (sublineage 3.5) were prevalent only in mainland China. According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 16 , 23 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China.…”
Section: Resultssupporting
confidence: 78%